Interstate Migration and Wage Theory - Raimon, Robert L. (The Review of Economics and Statistics, 1962)
E M PI RI CALLYBASED generalizations about labor mobility patterns usually are generalizations about that minority of the labor force which consists of hourly-rated manual workers. These generalizations are further limited in most instances to the patterns described by such workers within local labor markets. Such are the confines, for the most part, of the mobility literature a literature inspired by distrust of and dissatisfaction with the conventional model.1 Subject to the constraining influence exerted by the emphasis on market imperfections of the empirical studies, however, our generalizations about mobility for the majority of the labor force and for movement by manual workers among labor markets, rest essentially on our expectations that the predictive implications of the classical model would not be disappointed were they tested. This paper subjects one aspect of those expectations to a test centered around net civilian migration by state in relation to earnings levels by state. In lieu of wage differences as the allocator of labor supplies, the labor market studies, especially the New Haven study, have advanced the job vacancy thesis workers respond to job openings. Wage differences are regarded as of little importance in the allocation process in the sense that the adjustment of labor supplies to the changing needs of industry is more or less independent of wage differences. Because the focus of the present study is on long distance mobility, interstate movement, the following expression of the job vacancy thesis is particularly relevant: